2020
DOI: 10.1002/jwmg.21818
|View full text |Cite
|
Sign up to set email alerts
|

Nest Site Selection Influences Cinnamon Teal Nest Survival in Colorado

Abstract: Nest survival of ducks is partially a function of the spatiotemporal characteristics of the site at which a bird chooses to nest. Nest survival is also a fundamental component of population growth in waterfowl but is relatively unstudied for cinnamon teal (Spatula cyanoptera). We investigated cinnamon teal nest survival in a managed wetland complex in southern Colorado, USA, and assessed nest site selection to determine whether nest site characteristics were adaptive. We monitored 85 nests in 2015–2017 on Mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 85 publications
2
8
0
Order By: Relevance
“…We also found that ducks preferred to nest in intermediate wheatgrass to other plants. In Colorado, cinnamon teal nested in grassy areas and avoided forbs, a trait that contributed to nest success; teal also exhibited a preference for Baltic rush ( Juncus arcticus ; Setash et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that ducks preferred to nest in intermediate wheatgrass to other plants. In Colorado, cinnamon teal nested in grassy areas and avoided forbs, a trait that contributed to nest success; teal also exhibited a preference for Baltic rush ( Juncus arcticus ; Setash et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Limited knowledge of cinnamon teal nest site selection has hindered efforts to create suitable nesting habitat for cinnamon teal (Setash et al 2020). We examined nest‐site selection of waterfowl using GSL wetlands.…”
mentioning
confidence: 99%
“…The ability to estimate survival during different periods (i.e. states) for each individual is important for comparing survival among breeding stages at any given date (Arnold et al 2012, Setash et al 2020). The model I used was a straightforward, intuitive way of including breeding stage because each day can be assigned a different level of a categorical variable.…”
Section: Discussionmentioning
confidence: 99%
“…When we located a nest, we recorded GPS coordinates (Garmin GPSMAP 64sx GPS: Garmin, Olathe, KS, USA), counted eggs, and estimated incubation stage (Rush et al 2007). As part of a concurrent nest survival study (Dykstra 2023), we checked nests every 5–7 days (Borgo and Conover 2016, Setash et al 2020).…”
Section: Methodsmentioning
confidence: 99%